Virology research in a Latin American developing country: A bibliometric analysis of virology in Colombia (2000–2013) (2015)
Introduction: Bibliometric analysis demonstrates that the virology research in Latin America has increased. For this reason, the objective of this study was to evaluate Colombian publications on viruses and viral diseases in indexed journals during the period from 2000 to 2013. Methodology: The bibliographic data were collected from MedLine, SciELO, LILACS and Scopus databases. The database was constructed in Excel descriptive statistics. The SCImago Journal Rank (SJR) was evaluated using the SCImago Journal & Country Rank in 2013 and was used as an indicator of the quality of the journals used by the Colombian researchers. Results: The total number of papers published was 711, of which 40.4% were published in local journals, and 59.6% were published in foreign journals. Most (89.2%) were original papers. Moreover, 34.2% of the papers were published in collaboration with international researchers, with the United States being the most represented. Of the journals used, 85.6% had an SJR, and 14.4% did not. The median SJR of the papers was 0.789, and the median of the papers with international collaborators was higher compared to the SJR of the papers without international collaboration. Papers were most frequently published in journals whose categories were medicine (miscellaneous), virology, and infectious diseases. The viruses that appeared in the papers more frequently were HIV, dengue, and papillomavirus. Conclusions: This study provides data for use in research, health planning, and policy analysis as it relates to virology in Colombia and other developing Latin American countries. © 2015 Ruiz-Saenz et al.